2018
DOI: 10.1101/442624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous aggressive ERα+ mammary tumor model is driven by Kras activation

Abstract: The NRL-PRL murine model, defined by mammary-selective transgenic rat prolactin ligand rPrl expression, establishes spontaneous ER+ mammary tumors, mimicking the association between elevated prolactin (PRL) and risk for development of ER+ breast cancer in postmenopausal women. Whole genome and exome sequencing in a discovery cohort (n=5) of end stage tumors revealed canonical activating mutations and copy number amplifications of Kras . The frequent mutations in this pathway were validated in an extension coho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The TC11 cell line was generated from an ER+ mammary tumor that developed in a NRL-PRL female [19]. Like the parent tumors that develop spontaneously as a result of local transgenic prolactin overexpression in the mammary glands [18,20], TC11 cells express low levels of progesterone receptor, but respond to E2 with robust proliferation and changes in gene expression [19]. For some of these studies, 10 000 TC11 cells in 50 μl of sterile PBS were orthotopically injected bilaterally into the caudal mammary fat pads of 10-week-old WT or mCol1a1 FVB/N female mice.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TC11 cell line was generated from an ER+ mammary tumor that developed in a NRL-PRL female [19]. Like the parent tumors that develop spontaneously as a result of local transgenic prolactin overexpression in the mammary glands [18,20], TC11 cells express low levels of progesterone receptor, but respond to E2 with robust proliferation and changes in gene expression [19]. For some of these studies, 10 000 TC11 cells in 50 μl of sterile PBS were orthotopically injected bilaterally into the caudal mammary fat pads of 10-week-old WT or mCol1a1 FVB/N female mice.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The paucity of immunocompetent models of ER+ aggressive disease has limited our ability to probe the effects on behavior of primary ER+ tumors and disseminated tumor cells. Here we utilized a hormonally-induced mouse model of ER+ breast cancer, which displays many characteristics of aggressive luminal B clinical cancers [18][19][20]. We used an ER+ cell line derived from these estrogen responsive metastatic cancers , in conjunction with a model of elevated collagen deposition, Col1a1 tm1Jae/+ (mCol1a1) [21], to mimic the desmoplasia surrounding growing tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing data from genetically engineered mouse models is largely lacking, with only a few models having been sequenced [28,[31][32][33]. SNV mutation rates between previous studies and ours indicate similarities, and the small discrepancies may be explained through differences in data processing methods.…”
Section: Discussionmentioning
confidence: 46%
“…Another study revealed that two small molecule inhibitors, SMI-1 and SMI-6, abrogated PRL-induced HER2 + breast cancer cell invasion and malignant lymphocyte proliferation by binding the extracellular domain of PRLR (63). Moreover, PRL synergizes with canonical WNT signals and KRAS activation to drive the development of ER + mammary tumors, by activating the Notch signaling pathway (64,65). MacDonald et al reported that PRL-inducible EDD E3 ubiquitin ligase promotes TORC1 signaling, anti-apoptotic protein expression, and drug resistance in mammary tumors (66).…”
Section: Research Progress In Prl and Female Prl-related Tumorsmentioning
confidence: 99%